BAURAN PEMASARAN OLAHAN LIDAH BUAYA TERHADAP KEPUTUSAN PEMBELIAN SECARA E-COMMERCE UKM I SUN VERA - Suryati, Lili; Dolorosa, Eva; Oktoriana, Shenny (SOCA: Jurnal Sosial Ekonomi Pertanian, 2020)
The rapid growth in internet users in Indonesia makes the e-commerce business increasingly fierce by business people. UKM I Sun Vera is one of the UKM that develops e-commerce marketing business of processed aloe vera products, but in the implementation of UKM I Sun Vera still experience some obstacles such as sales promotions carried out less than the maximum, less skilled labor, limited knowledge of applications or online business systems so that consumer purchasing decisions in e-commerce are low on the product I SUN VERA. The purpose of this study was to analyze the effect of aloe vera marketing mix on the purchasing decision of e-commerce UKM I Sun Vera. This study used a survey method with quantitative descriptive analysis namely Structural Equation Modeling (SEM) with LISREL 8.80 software. Sampling technique used on this research is purposive sampling, that involved 110 respondents. Data were collected through e-questionnaire with google form. The results showed that the variable marketing mix of products, prices and processes influence purchasing decisions. UKM I Sun Vera must pay attention to the nutritional content of the product on the packaging and add variety to the product uploaded in online marketing media. Sun Vera I SMEs must also pay attention to the affordability of product prices by making product innovations in various sizes and shapes and by adding online payment alternatives to facilitate consumers in terms of payment such as Dana, Gopay, Alfamart / Indomaret, Cash On Delivery and others.